Multicenter comparison of double‐balloon enteroscopy and spiral enteroscopy. Issue 6 (22nd May 2013) - Rahmi, Gabriel; Samaha, Elia; Vahedi, Kouroche; Ponchon, Thierry; Fumex, Fabien; Filoche, Bernard; Gay, Gerard; Delvaux, Michel; Lorenceau‐Savale, Camille; Malamut, Georgia; Canard, Jean‐Marc; Chatellier, Gilles; et al.
Abstract Background and Aim Spiral enteroscopy is a novel technique for small bowel exploration. The aim of this study is to compare double‐balloon and spiral enteroscopy in patients with suspected small bowel lesions. Methods Patients with suspected small bowel lesion diagnosed by capsule endoscopy were prospectively included between September 2009 and December 2010 in five tertiary‐care academic medical centers. Results After capsule endoscopy, 191 double‐balloon enteroscopy and 50 spiral enteroscopies were performed. Indications were obscure gastrointestinal bleeding in 194 (80%) of cases. Lesions detected by capsule endoscopy were mainly angioectasia. Double‐balloon and spiral enteroscopy resulted in finding one or more lesions in 70% and 75% of cases, respectively. The mean diagnosis procedure time and the average small bowel explored length during double‐balloon and spiral enteroscopy were, respectively, 60 min (45–80) and 55 min (45–80) (P = 0.74), and 200 cm (150–300) and 220 cm (200–300) (P = 0.13). Treatment during double‐balloon and spiral enteroscopy was possible in 66% and 70% of cases, respectively. There was no significant major procedure‐related complication. Conclusion Spiral enteroscopy appears as safe as double‐balloon enteroscopy for small bowel exploration with a similar diagnostic and therapeutic yield. Comparison between the two procedures in terms of duration and length of small bowel explored is slightly in favor of spiral enteroscopy but not significantly.